Gaya Kepemimpinan Transformasional dan Service Excellent pada Perawat di Rumah Sakit Ken Saras Kabupaten Semarang - Paulus Budi Santoso; Sudiro Sudiro (Jurnal Manajemen Kesehatan Indonesia, 2020)
The preliminary study at the Ken Saras Hospital showed the nurses have verbal errors, long admission, and treatment incompliance with the standard. This problem was assumed to be related with the room coordinator's leadership style. Hence, this study identified the effect of the coordinator's leadership style towards nurses responsiveness on the healthcare services at the Ken Saras hospital.This was an observational and Quantitative study using a cross sectional design. There were 70 nurses as samples who are incharge of giving treatment and having been trained about service excellence. The dependent variable is nurses' responsiveness, and the ondependent one is room coordinator's transformational leadership. The validity and reability of the instruments for this study have been tested at the same-type hospital. The data were analyzed gradually starting from univariate analysis, bivariate analysis using chi-square, and multivariate analysis using logistic regression test.The univariate analysis performed that the lroom coordinator's leadership was  good, but it lacked in  inspirational motivation and individual consideration. Whereas, the bivariate analysis found there is a relationship between the sub-variable of idealized influence  and nurses' response on excellence service. Finally, the multivariate analysis further noticed that all variable of transformational leadership style have no significant effect towards nurses’ responsiveness on service execellence It is suggested that the management of Ken Saras hospital improve the leadershiop skill of the room coordinator. especially of the aspects of inspirational motivation and individualized consideration. also, the management should consider the candidate's characteristics choosen to be a room coordinator